Multiple hospital organisational factors are associated with adverse patient outcomes post-hip fracture in England and Wales: the REDUCE record-linkage cohort study. (31st August 2022) - Patel, Rita; Judge, Andrew; Johansen, Antony; Marques, Elsa M R; Griffin, Jill; Bradshaw, Marianne; Drew, Sarah; Whale, Katie; Chesser, Tim; Griffin, Xavier L; Javaid, Muhammad K; Ben-Shlomo, Yoav; et al.
Abstract: Objectives: Despite established standards and guidelines, substantial variation remains in the delivery of hip fracture care across the United Kingdom. We aimed to determine which hospital-level organisational factors predict adverse patient outcomes in the months following hip fracture. Methods: We examined a national record-linkage cohort of 178, 757 patients aged ≥60 years who sustained a hip fracture in England and Wales in 2016–19. Patient-level hospital admissions datasets, National Hip Fracture Database and mortality data were linked to metrics from 18 hospital-level organisational-level audits and reports. Multilevel models identified organisational factors, independent of patient case-mix, associated with three patient outcomes: length of hospital stay (LOS), 30-day all-cause mortality and emergency 30-day readmission. Results: Across hospitals mean LOS ranged from 12 to 41.9 days, mean 30-day mortality from 3.7 to 10.4% and mean readmission rates from 3.7 to 30.3%, overall means were 21.4 days, 7.3% and 15.3%, respectively. In all, 22 organisational factors were independently associated with LOS; e.g. a hospital's ability to mobilise >90% of patients promptly after surgery predicted a 2-day shorter LOS (95% confidence interval [CI]: 1.2–2.6). Ten organisational factors were independently associated with 30-day mortality; e.g. discussion of patient experience feedback at clinical governance meetings and provision of prompt surgery to >80% of patients were each associated with 10% lower mortality (95%CI: 5–15%). Nine organisational factors were independently associated with readmissions; e.g. readmissions were 17% lower if hospitals reported how soon community therapy would start after discharge (95%CI: 9–24%). Conclusions: Receipt of hip fracture care should be reliable and equitable across the country. We have identified multiple, potentially modifiable, organisational factors associated with important patient outcomes following hip fracture.